First Generation Students in the Hungarian Higher Educational System - Bocsi, Veronika (Central European Journal of Educational Research, 2020)
The first part of the study attempts to summarise the most frequently used and cited theories and empirical findings in the field of first generation students. The specialist literature has identified those factors (cultural background of family, parents’ special attitude toward learning, the features of the time-budget etc.) which can generate a disadvantageous situation within the higher education system for these students. However, the presence of this group is a significant indicator of the openness of a society and social mobility, and a more careful analysis of this population may reduce the drop-out rate, as well. During the empirical analysis two databases were used (Eurostudent VI, Hungarian Youth Research 2012 and 2016). Our results draw attention to the process of social closure and the decreasing chance of attending higher education for young people from lower social groups. This unfavourable shift can mirror the relatively closed features of Hungarian society, but at the same time it can make the distances among social groups more rigid.